Comparative Study On ‘Dietary Education’ In Japan And Korea: From The Latest Nutritional Knowledge Perspective - Tamie Saeki (International Journal of Global Health, 2024)
According to the Japan’s National Health and Nutrition Survey, trends in the intake of vegetables and fruits (1999-2018), which are considered effective in preventing lifestyle-related diseases, are far below the target value; In the under-50 age group, less than 30% achieved the target vegetable intake of 350g, and less than 15% achieved the target fruit intake of 200g 53. Against such background, it has become a challenge to nurture children's ‘self-management ability’ that leads to spontaneous and healthy dietary habits 16. Until now, almost all research on ‘Dietary education’ has been conducted in the field of nutrition, focusing on accumulating nutritional knowledge by explaining each nutritional component and its function. However, it is difficult to nurture spontaneous and healthy dietary habits simply through repeated nutrition-based education. It can be said that the pedagogical approach of this paper has made it possible to pursue from a broader perspective that influences food choices. Research on ‘nutrition transition’ points out “worldwide obesity dynamics and their determinants” based on “a shift in the broader patterns of dietary habits (Western-style diet) and corresponding nutrition-related diseases” 42. Nutrition transition research 5040 has a broad and holistic perspective on food and health, making it easy to understand nutrition. The purpose of this paper is to pursue how to nurture the ‘self-management ability’ for spontaneous and healthy dietary habits, based on these latest nutritional knowledges. Because nutrition transition is a global phenomenon, the author choses to use broader methods of international comparative research. Comparisons lead to discoveries and value creation. This can be said to have the greatest significance in comparative research.
Keywords: lifestyle-related diseases